Two Portuguese Cochlear Implanted Dizygotic Twins: A Case Report - Joana Rita Chora; Helena Simões-Teixeira; Tiago Daniel Matos; Jorge Humberto Martins; Marisa Alves; Raquel Ferreira; Luís Silva; Carlos Ribeiro; Graça Fialho; Helena Caria (Case Reports in Genetics)
Individual’s hearing performance after cochlear implant (CI) is variable and depends on different factors such as etiology of deafness, age at implantation, and social/family hearing environment. Here we report the case of dizygotic twins, boy and girl, presenting with neurosensorial profound deafness prior CI (age of implantation = 3.5 years old). Both parents have severe/profound deafness, since childhood, and use sign language as primary mode of communication. Clinical and genetic characterization was performed, as well as the assessment of the auditory and oral (re)habilitation after CI, applying a battery of audiological, speech, and language tests. The twin girl and the father were homozygous for the c.35delG mutation in the GJB2 gene, while the twin boy and the mother were compound heterozygotes, both monoallelic for c.35delG and for the deletion del(GJB6-D13S1830) in the GJB6 gene. The remaining hearing impaired relatives were c.35delG homozygotes. The genetic cause of deafness was thus identified in this family. Some noteworthy differences were observed regarding twins’ auditory and oral performance after CI. Subsequent follow-up of these children allowed us to conclude that those differences were most likely due to the different environment in which the twins have been living than to their different GJB2/GJB6 genotypes.